Comment traduire en japonais les styles indirect et indirect libre de Madame Bovary ? - Hisaki Sawasaki (Flaubert: Revue Critique et Génétique)
We will examine the difficulties met when translating Western literary texts in Japanese, in particular the problem of indirect and free indirect styles. We will define the grammatical issue and compare seven translations of Madame Bovary, published over a fifty year period. This time can be likened to a long path taken to digest the Western notion of direct and indirect styles, while reconciling it with Japanese language characteristics. On the other hand the translators’ relentless work has somewhat influenced the Japanese language. The annex will present all the Japanese texts examined.